2007
DOI: 10.1136/jnnp.2006.111476
|View full text |Cite
|
Sign up to set email alerts
|

Proxy and self-report agreement on the Stroke and Aphasia Quality of Life Scale-39

Abstract: Background and purpose: Health related quality of life outcomes are increasingly used to measure the effectiveness of stroke interventions. People with severe aphasia after stroke may be unable to self-report on such measures, necessitating the use of proxy respondents. We explored the level of agreement between people with aphasia (PWA) and their proxies on the Stroke and Aphasia Quality of Life Scale (SAQOL-39) and whether this agreement is influenced by demographic variables and proxy levels of depression a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
79
3
2

Year Published

2009
2009
2016
2016

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 122 publications
(97 citation statements)
references
References 16 publications
13
79
3
2
Order By: Relevance
“…In our study, caregivers rated patients as more depressive than did the patients themselves, although there was some correlation between the caregiver ratings and patient ratings. This result is in line with studies on the quality of life among patients with stroke, 35,36 in which proxies tended to score the patients as more severely affected than the patients scored themselves. In our study, this disagreement 6 and 18 months after stroke was higher when the caregivers themselves had high BDI scores and patients low BDI scores.…”
Section: Discussionsupporting
confidence: 88%
“…In our study, caregivers rated patients as more depressive than did the patients themselves, although there was some correlation between the caregiver ratings and patient ratings. This result is in line with studies on the quality of life among patients with stroke, 35,36 in which proxies tended to score the patients as more severely affected than the patients scored themselves. In our study, this disagreement 6 and 18 months after stroke was higher when the caregivers themselves had high BDI scores and patients low BDI scores.…”
Section: Discussionsupporting
confidence: 88%
“…In one study, ∼ 25% of stroke survivors were excluded from QoL assessment because of aphasia or cognitive impairments (Kwa, Limburg, & de Haan, 1996). For this reason, there is support for proxy judgements in which another person reports for the person with communication disability (Hilari & Byng, 2009;Hilari, Owen, & Farrelly, 2007). However, most caution against proxy judgements on personal or subjective domains (e.g., Carod-Artal, Coral, Trizzoto, & Moreira, 2009).…”
Section: Development Of the Assessment For Living With Aphasiamentioning
confidence: 99%
“…People with aphasia are excluded from most stroke research exploring social networks (Northcott et al, 2015). Even where people with aphasia have been included, often researchers have relied on proxies (Astrom et al, 1993;Boden-Albala et al, 2005) although there are concerns that proxy responses are not commensurate with self-report (Hilari, Owen, & Farrelly, 2007). This may potentially bias results: a recent retrospective analysis of pooled clinical trial data (n = 8,904) reported that 45% of stroke survivors initially presented with aphasia, and by three months the aphasia persisted for 24% of stroke survivors (Ali, Lyden, & Brady, 2015).…”
Section: Introductionmentioning
confidence: 99%